2017
DOI: 10.1089/sur.2017.101
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review of Criteria for Defining Recipient-Site Infection after Oral Oncologic Surgery with Simultaneous Reconstruction

Abstract: Reconsideration of the categorization of orocutaneous fistula as infection, regardless of the etiology, and differentiation of superficial and deep incisional infections are necessary for correct assessment of recipient-site infection in oral oncologic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In our study, flap dehiscence and fistula were the most common minor complications (17.5% overall, 10% in group A and 30% in group B). The main risk factors associated with fistula are ascribable to patient-related factors, such as poor nutritional status, systemic conditions that compromise wound healing (diabetes mellitus), previous treatments (radiotherapy and/or chemotherapy) and to surgical site-related factors, such as the clean/contaminated environment of the oral cavity (saliva and bacterial flora), infections, size of the defects after extensive resection and ischaemic complications of the flap 10 . Flap dehiscence with orocutaneous fistula after microvascular tongue reconstruction is a complication that decreases the patient’s quality of life, with prolonged hospitalisation and delayed start of adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, flap dehiscence and fistula were the most common minor complications (17.5% overall, 10% in group A and 30% in group B). The main risk factors associated with fistula are ascribable to patient-related factors, such as poor nutritional status, systemic conditions that compromise wound healing (diabetes mellitus), previous treatments (radiotherapy and/or chemotherapy) and to surgical site-related factors, such as the clean/contaminated environment of the oral cavity (saliva and bacterial flora), infections, size of the defects after extensive resection and ischaemic complications of the flap 10 . Flap dehiscence with orocutaneous fistula after microvascular tongue reconstruction is a complication that decreases the patient’s quality of life, with prolonged hospitalisation and delayed start of adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive power of ANN was not validated in other populations, and therefore its generalizability could not be correctly determined. Finally, there is lack of uniformity of criteria for defining the SSI [ 55 ]. For example, the orocutaneous fistulas that did not meet the CDC criteria were not categorized as an SSI in some studies [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the orocutaneous fistulas that did not meet the CDC criteria were not categorized as an SSI in some studies [ 56 , 57 ]. However, some authors suggested that orocutaneous fistula caused by apparent infection such as abscess formation should be categorized as post-operative SSI [ 55 ]. The selection of different definition of SSI may cause a bias in the study.…”
Section: Discussionmentioning
confidence: 99%